2014
DOI: 10.1111/nph.13146
|View full text |Cite
|
Sign up to set email alerts
|

Summer drought alters carbon allocation to roots and root respiration in mountain grassland

Abstract: Drought affects the carbon (C) source and sink activities of plant organs, with potential consequences for belowground C allocation, a key process of the terrestrial C cycle. The responses of belowground C allocation dynamics to drought are so far poorly understood.We combined experimental rain exclusion with 13C pulse labelling in a mountain meadow to analyse the effects of summer drought on the dynamics of belowground allocation of recently assimilated C and how it is partitioned among different carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
179
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 223 publications
(183 citation statements)
references
References 68 publications
4
179
0
Order By: Relevance
“…Stomatal closure at low water and subsequent decline in transpiration (Table ) could lead to reduced photosynthesis, and therefore, decreased plant‐derived SOC (Figure b) and plant‐derived C in microbial biomass (MBC PLANT ) through rhizodeposition (Figure a). These results are consistent with several other studies showing that drought can severely reduce belowground C allocation (Hasibeder, Fuchslueger, Richter, & Bahn, ; Sanaullah, Rumpel, Charrier, & Chabbi, ), which in return affect microbe‐mediated C turnover (Canarini & Dijkstra, ; Fuchslueger et al., ). While high temperature usually triggers stomatal closure after soils have dried out (Lahr, Schade, Crossett, & Watson, ; Weston & Bauerle, ), in our study, we frequently watered pots to maintain soil moisture at 15% and 25%, and therefore, photosynthesis may have continued resulting in increased plant‐derived SOC to the soil at high temperature compared to low temperature (Figure b).…”
Section: Discussionsupporting
confidence: 92%
“…Stomatal closure at low water and subsequent decline in transpiration (Table ) could lead to reduced photosynthesis, and therefore, decreased plant‐derived SOC (Figure b) and plant‐derived C in microbial biomass (MBC PLANT ) through rhizodeposition (Figure a). These results are consistent with several other studies showing that drought can severely reduce belowground C allocation (Hasibeder, Fuchslueger, Richter, & Bahn, ; Sanaullah, Rumpel, Charrier, & Chabbi, ), which in return affect microbe‐mediated C turnover (Canarini & Dijkstra, ; Fuchslueger et al., ). While high temperature usually triggers stomatal closure after soils have dried out (Lahr, Schade, Crossett, & Watson, ; Weston & Bauerle, ), in our study, we frequently watered pots to maintain soil moisture at 15% and 25%, and therefore, photosynthesis may have continued resulting in increased plant‐derived SOC to the soil at high temperature compared to low temperature (Figure b).…”
Section: Discussionsupporting
confidence: 92%
“…In the wetter savanna systems of the humid region (>750 mm of mean annual precipitation, MAP), it has been shown that a considerable amount of C is stored in the roots at the start of the dry season and is subsequently used by the herbaceous vegetation to re-sprout at the start of the next growing season [76]. If the dry season is intense, prolonged, or both, this memory effect allows vegetation to tap into these C reserves and maintain root respiration [77]. A recent global study by Murray-Tortarolo et al [78] lends support to this, finding that the intensity and duration of the dry season has a larger impact on annual primary productivity than increased rainfall in the rainy season.…”
Section: Relationship Between Ec Gpp Paw Vpd and Apimentioning
confidence: 99%
“…Drought events (Fuchslueger et al., ; Hasibeder et al., ) and grassland management (Grigulis et al., ; Schmitt et al., ), taken independently, affect C and N cycling in mountain grasslands. However, the combined effects of drought and grassland management intensity and how they affect the resistance and resilience of the grassland community are not well known.…”
Section: Introductionmentioning
confidence: 99%